Models of start-up thinking and action theoretical, empirical and pedagogical approaches - Katz, Jerome A.; Corbett, Andrew C. (Advances in entrepreneurship, firm emergence and growth ;, 2016)
Volume 18 will focus on approaches to thinking about and creating the start-up. Both theoretical and empirical manuscripts that consider all aspects of start-up planning, thinking and action will be considered. We also encourage practice-based research and manuscripts that explore cutting-edge pedagogical approaches. The papers in Advances reflect many state-of-the-art topics and approaches, and are written by leading researches in the field, making each volume an important source of information for virtually all entrepreneurship researchers. One of the distinctive competences of research volumes such as Advances is that the chapters can be published without page restrictions allowing for greater detail in the background, development, and implementation of ideas than is possible in journal articles. This provides authors with the opportunity to fully express their key ideas, provide much more complete support, and include relevant multi-page appendices. In effect, the Advances series provides authors the opportunity to publish an "article of record" of their major theoretical or empirical ideas, and see it disseminated to a wide audience.